(untitled) (Research, Society and Development, 2026)
Objective: To identify the presence of healthcare clusters and differences according to municipal population size and the coefficient of physiotherapists providing care through the Brazilian Health System (CoFSUS). Methods: This ecological study employed quantitative and spatial analyses of secondary data from 5,570 municipalities using the 2024 records of the Outpatient Information System (SIA) and the National Registry of Health Establishments of the Unified Health System (SUS). Nonparametric tests and spatial autocorrelation analyses were applied to identify patterns and clusters. Results: Physiotherapy services were recorded in the SIA for 58.9% (3,281) of Brazilian municipalities. Coverage was lower in small municipalities (47.1%), although these showed the highest mean [0.37 – SD (0.44)] and median 0.25 [Q1 (0.11)–Q3 (0.48)] for the Outpatient Care Coefficient (CoA). A very weak correlation (r = 0.167, p < 0.01) was found between CoA and CoFSUS per 1,000 inhabitants. Spatial analysis revealed a weak positive correlation (global Moran’s I = 0.11) and clusters of healthcare service gaps. Conclusion: The availability of outpatient physiotherapy services within Brazil’s public healthcare system is asymmetrical and does not depend on municipal population size or the proportion of physiotherapists.